Water Purification: Sphagnum Inspired g‐C3N4 Nano/Microspheres with Smaller Bandgap in Heterojunction Membranes for Sunlight‐Driven Water Purification (Small 12/2021). Issue 12 (25th March 2021) - Ji, Lingtong; Yan, Luke; Chao, Min; Li, Mengru; Gu, Jincui; Lei, Miao; Zhang, Yanmei; Wang, Xun; Xia, Junyuan; Chen, Tianyu; Nie, Yujing; Chen, Tao
Abstract : In article number 2007122, Min Chao, Jincui Gu, Xun Wang, Tao Chen, and co‐workers present an advanced all‐in‐one separation membrane, which can realize continuous water purification with stable separation performance, catalytic degradation ability, antibacterial capacity and excellent self‐cleaning ability, suggesting its potential value for purifying realistic complex wastewater.